Biology, trophic chain, and ethnobiological calendar of the mangrove crab, Ucides cordatus (Linnaeus, 1763) (Brachyura, Ocypodidae), according to the perception of catchers in Itanhaem, Sao Paulo, Brazil - Souza, Fernanda Vargas Barbi de [UNESP]; Pinheiro, Marcelo Antonio Amaro [UNESP] (Soc Brasileira Carcinologia, 2022)
Ethnobiology helps to better understand research processes involving humans and nature. It produces important information for the management of ecosystems and their natural resources. The mangrove crab (Ucides cordatus) is an endemic mangrove crustacean that lives in close association with arboreal vegetation and whose distribution extends throughout this ecosystem along the Brazilian coast. It plays an important role in ecosystem processes, actively participating in sediment bioturbation and the flow of organic matter and energy, affecting the entire trophic chain of coastal environments. This study compiles ethnobiological data from catchers in the Itanhaem River Estuary (state of Sao Paulo) on the biology of the mangrove crab according to morphotype (male and female), biological cycle (growth and reproductive period), fishing season, and its participation in the trophic chain of mangroves. Thus, this study serves as a basis for education and environmental management actions. The authors conducted interviews using the snowball technique and applied a semi-structured questionnaire with open and closed questions for catchers. We submitted the data to qualitative and quantitative analysis and compared it with data from the available literature. We interviewed the entire sample universe of catchers in the study area. Ethnobiological data referring to the periods of growth and reproduction coincided with literature data in the following proportions: 66.8 % for Brazil and 82.5 % for the southeast-south region. The results reinforce the relevance and accuracy of local ecological knowledge in the interpretation of data from nature. Moreover, the results show gaps in compliance with the norms for the protection of this species.
Keywords: Artisanal fishery; Collective subject discourse; Fishermen; Food chain; Local ecological knowledge